Consideration of kala in panchakarma - Shruthi .S; Swati. S. Despande; Vinay Kumar.K.N (International Journal of Pharmacy and Analytical Research, 2022)
Ayurvedic system of medicine aims at maintenance of health in a healthy individual and alleviation of diseases in a diseased person. Thus Ayurveda helps in attaining the Purusharthas. That is why, Ayurveda being science of life, gives emphasis on the concept of Kala. Ayurveda has given great importance to the kala for the swastha as well as the atura. Though, Kala has relationship with all the effects, to prove it practically in the clinical aspect, the problem was undertaken. In accordance, Acharya Charaka says that Aushadha given at appropriate Kala is more efficacious than one given at inappropriate Kala. The importance of kala has been highlighted in Ayurveda on which dosha, agni, bala, ahara, vyadhi, oushadha and chikitsa. Thus even in panchakarma procedure kala plays an important role.